Search bugging devices by telephone line nonlinear locations - Лыков, Юрий Владимирович (Eastern-European Journal of Enterprise Technologies, 2012)
The purpose of this study is to examine the method of nonlinear location, research its ability to search of bugging devices on the phone line. In paper gives theoretically rationale and simulation in the CAD of method nonlinear location for search of bugging device in the telephone line. As a result, circuit simulation obtained conclusions: The range of harmonic distortion for elementary physical models of bugging devices and real circuit of bugging devices is the between of 0.01 to 1.5. Factors such as ambient temperature and length of the telephone line is insignificant (less than 15%) is affected by the value of harmonic distortion. The method of nonlinear location the telephone line to detect the connection, most used criminals’ phone bugging devices